Hippocratic Oath / Hipokratova prisega - Pahor, Dušica (Acta Medico-Biotechnica, 2022)
After completing our medical studies, we all swore to honor the Hippocratic Oath. To this day, the Hippocratic Oath is still sworn by new generations of young physicians. I am not sure if we are aware that the Hippocratic Oath is vital for all physicians because it defines and outlines our mission. The Hippocratic Oath constitutes our way of living, thinking, and acting, and thus deserves to be respected. Modern medicine, which is becoming increasingly dehumanized and profit-driven, must not mislead us. Not even when one of the most significant thoughts in the Hippocratic Oath – I will give no deadly medicine to anyone if asked, nor suggest any such counsel – might be dismissed due to a noble intention to help the dying.Do we understand what this oath demands, where it leads us to, how it guides us, and helps us make judgments when temptations in our daily lives may take us down a wrong path? Do we know how much truth lies in this oath, how much thought is still relevant today, and how many life orientations fulfill the mission of every single physician?
Keywords: Hippocratic Oath